Membangun Kesadaran Pola Hidup Sehat pada Anak-Anak Desa Kilang, Lombok Timur - Aprilia, Suryani (Primary Journal of Multidisciplinary Research, 2025)
Awareness of the importance of a healthy lifestyle among children serves as a fundamental basis for building a healthy and productive generation. This study aims to identify effective strategies for raising awareness among children in Kilang Village, East Lombok, regarding the importance of healthy living habits. A qualitative descriptive approach was employed, with data collected through observation, interviews, and focus group discussions. The research subjects included children aged 6–12 years, as well as educators and parents as primary supporters. The findings revealed that the low level of awareness among children about healthy living habits is due to a lack of understanding, limited access to information, and unsupportive family habits. Community-based educational programs involving interactive activities, such as educational games and healthy eating simulations, proved effective in enhancing children's awareness. Furthermore, parental and community leader support plays a crucial role in sustaining the implementation of healthy living practices. The study concludes that a participatory and collaborative approach involving children, families, and the community is key to sustainably building awareness of healthy lifestyle habits. Recommendations are provided to expand this program to other areas with similar characteristics